Pemenuhan Keadilan Lingkungan dalam Penerapan Kebijakan Tata Ruang Wilayah Kota Palembang - Azhar Azhar; Abdul Halim; Cynthia Azhara Putri (PERSPEKTIF, 2023)
This article aims to analyze the fulfillment of Ecological Justice in the implementation of spatial policy in Palembang City based on the implementation of the international regime, namely SDG's point 11. The achievement of sustainable cities is a focus to see how the fulfillment of environmental justice is formed in the process of implementing regional spatial policy carried out in Palembang city. Using Kuehn's concept of Ecological Justice, look at the implementation of regional spatial policy with four aspects, namely distributive, corrective, procedural and social. An exploratory descriptive qualitative method with data collection techniques used literature studies and interviews. The findings obtained include the implementation of distributive justice with various programs, however, the problem that is still the main obstacle is the need to pay attention to the city's green areas. In corrective justice, environmental policies already exist, but it is necessary to maximize law enforcement. In implementing procedural justice, policies are made that do not focus on targeting elements of community needs. The involvement of the community and NGOs in policy-making is still minimal. In terms of social justice, there is still a lot of community production land, open green areas, and protected land such as swamp land which is used as economic and residential areas which are exacerbated by regulations issued by the government which is a source of environmental damage. Through the findings above, it is hoped that policy formulation and implementation processes can be further maximized to achieve environmental justice in Palembang City.